2020
DOI: 10.1186/s12888-020-02566-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of yoga on sleep quality and insomnia in women with sleep problems: a systematic review and meta-analysis

Abstract: Background: To examine the effectiveness and safety of yoga of women with sleep problems by performing a systematic review and meta-analysis. Methods: Medline/PubMed, ClinicalKey, ScienceDirect, Embase, PsycINFO, and the Cochrane Library were searched throughout the month of June, 2019. Randomized controlled trials comparing yoga groups with control groups in women with sleep problems were included. Two reviewers independently evaluated risk of bias by using the risk of bias tool suggested by the Cochrane Coll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 76 publications
3
72
0
6
Order By: Relevance
“…69 Considering women with sleep problems, Wang and coworkers reported that yoga intervention could be beneficial in the long-term. 70 Furthermore, yoga practice has also been reported to be helpful in primary insomnia, 71 and it was shown to improve sleep in elderly people, 72 cancer patients, 73 and women with menopausal symptoms. 74 However, European guidelines for the diagnosis and treatment of insomnia 14 do not recommend yoga for the treatment of insomnia because of poor evidence.…”
Section: Exercisementioning
confidence: 99%
“…69 Considering women with sleep problems, Wang and coworkers reported that yoga intervention could be beneficial in the long-term. 70 Furthermore, yoga practice has also been reported to be helpful in primary insomnia, 71 and it was shown to improve sleep in elderly people, 72 cancer patients, 73 and women with menopausal symptoms. 74 However, European guidelines for the diagnosis and treatment of insomnia 14 do not recommend yoga for the treatment of insomnia because of poor evidence.…”
Section: Exercisementioning
confidence: 99%
“… Pan et al, 2015 27 China 16/930 Cochrane criteria 2007–2012 Integrated yoga;Iyengar yoga; Yoga of awareness Program; Patanjali’s yoga; Modified yoga; Restorative yoga; Viniyoga Supportive therapy; Wait-list; Health education; Usual care; Standard physiotherapy; Brief supportive therapy ①③⑤⑥⑧ Yoga is effective on sleep outcome,quality of life, anxiety and depression, but not effective on fatigue for patients recovering from breast cancer. Wang et al, 2020 28 China 19/1832 Cochrane criteria 2009– 2019 Iyengar Yoga; Asanas yoga; Viniyoga; Restorative yoga; Hatha yoga; Tibetan yoga; Mindful yoga; Yoga breathing exercise in warm water Wait-list; Health education; Usual care; Social support Yoga is an effective supportive treatment for cancer in sleep outcome. Sadja et al, 2013 29 USA 10/583 Not mentioned 2004– 2012 Iyengar yoga; Tibetan yoga; Yoga of awareness; Patanjali’s yoga tradition; Based on Hatha; Integrated yoga program Wait-list; Health education Yoga may be beneficial for reducing fatigue in women with breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…[ 8 ] Mounting evidence shows that Yoga helps people practice healthy eating, improves sleep quality, reduces stress levels, and motivates people to quit addictions like alcohol consumption and smoking. [ 9 10 11 12 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…Google is one of the most common search engines and “Google Trends” was first introduced in 2006 used to understand and predict disease outbreaks and study policy impacts. [ 4 5 6 7 8 9 10 11 12 13 14 15 16 ] Policymaking and implementation during the COVID-19 pandemic has been dynamic. [ 17 ] In our study, we aim to assess the implications of global policy dynamics and COVID-19 pandemic on trends in mental health problems and Yoga across the world using GT analysis.…”
Section: Introductionmentioning
confidence: 99%